Promoting Employment and Preserving Cultural Heritage: A Study of Handicraft Products Tourism in Pokhara, Nepal - Upadhyay, Prakash (Journal of Tourism & Adventure, 2020)
Handicraft s form a fundamental part of tourist experience representing local traditions and indigenous population’s talents and skills, income and job opportunities. This paper aims at exploring the role of handicraft products in promoting employment as well as preserving the cultural heritage of Pokhara. The study result reveals that there is a significant level of correlation and dependency between handicraft products and tourist’s arrival, job creation and the increase in income and social status of artisans and handicrafts shopkeepers. As a unique experience for tourists, handicraft products have enriched national economy, identity and promoted cultural heritage, uniqueness and authenticity, and cultural commercialization. However, handicraft is notjust about commercialization of cultural arts or displaying and selling products, it is about allowing tourists to truly understand the skill and the craft at rear and realize handicraft s unique tradition, linking tourists to artisans to facilitate them understand and appreciate the art. Further it is about how culture is recognized through display of a new self-representation or ‘enterprising spirit’, but not with the total loss of primordial ‘pure culture’ albeit an authenticity of hybrid culture. Lack of effective advertisement and marketing, inequitable price, scarcity of raw materials, intrusion of foreign goods, ineffective government policies are the crucial tribulations of handicraft products tourism in Pokhara. State policy improvement, increase in supply of raw materials, creative production and marketing are the ways that can promote handicraft market. It is necessary recognizing the prominence of handicraft products tourism as a prodigious agent for preservation of traditional craft, methods of production and an effective means of socio cultural and economic empowerment, cultural renovation and national identity building.